Bartonella bacilliformis, endemic pathogen of the Andean region, is intrinsically resistant to quinolones - del Valle L.J. (2010)
This work was partially funded by the AECID (Agencia Española de Cooperación Internacional para el Desarrollo) grant numbers A/3795/05, A/4892/06, A/9727/07 A/4817/06; ACCD (Agència Catalana de Cooperació al Desenvolupament, Generalitat de Catalunya) grant U2006; CCD-UPC (Centre de Cooperació per al Desenvolupament, Universitat Politècnica de Catalunya) to LJdV; and by the CONCYTEC (Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica, Perú) grant 189-2005-CONCYTEC-OAJ. JR's research is supported by grant CP05/0130 of the FIS (Fondo de Investigaciones Sanitarias). The authors thank M.J. Pons and Donna Pringle for assistance in the preparation of the final version of the manuscript. Conflict of interest: No conflict of interest to declare.